Accompagner la professionnalisation des artistes équestres : analyse du processus depuis un comité de pilotage - Éric Maleyrot
This paper presents a collaborative research, based on the work of a steering committee in charge of implementing an innovative training scheme to support the equestrian artists' (EA) professionalisation. The article analyses the exchanges in the five meetings from this committee with regard to the concept of professionalisation and the actor-network theory. The results show that the steering committee constitutes a relevant socio-scientific space to study the two heuristic and praxeological dimensions of this technological research. This space allows, under ethical conditions, not only the understanding of the institutional, political, social, cultural and economic stakes of the EA world but also the co-construction of a relevant training scheme and the production of results in an epistemic nature on the EAs' professionalisation process.